1970
DOI: 10.3126/kuset.v4i1.2886
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of PM<sub>10</sub> Concentration in Occupation Environment of Traffic Police Personnel in Pokhara Sub-Metropolitan City, Nepal

Abstract: Air pollution, particularly particulate pollution has been emerged as the major air quality issues in urban centers of Nepal including Pokhara. Pokhara is one of the major cities in Nepal located at 28.24 N, 83.99 E, and also one of the most popular tourist destinations. This study has been conducted to assess the traffic police personnel exposure to PM 10 (Particulate Matter of diameter 10 micron of less) in their occupational environment in Pokhara. This type study has been conducted for the first time in Po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 0 publications
0
5
0
1
Order By: Relevance
“…No clear cut reasons have been found for this high preterm birth, but air pollution can arguably have an important impact on this. Air pollution is rising as an occupational hazard in Nepal, both in Kathmandu and in other cities like Pokhara, especially in traffic police who are being continuously exposed to dusty roads [ 51 , 52 ]. Due to this pulmonary functions have been significantly worsened in the traffic police working in Kathmandu [ 53 ].…”
Section: Impact On Human Healthmentioning
confidence: 99%
“…No clear cut reasons have been found for this high preterm birth, but air pollution can arguably have an important impact on this. Air pollution is rising as an occupational hazard in Nepal, both in Kathmandu and in other cities like Pokhara, especially in traffic police who are being continuously exposed to dusty roads [ 51 , 52 ]. Due to this pulmonary functions have been significantly worsened in the traffic police working in Kathmandu [ 53 ].…”
Section: Impact On Human Healthmentioning
confidence: 99%
“…17 A previous study used personal monitors to measure PM 10 at three high-density traffic locations in Pokhara over 7 days, although measurements were of the location, not individuals, and the monitor was passed between traffic police (TP) at the same location as shifts changed. 18 This study showed the range of exposure for the location of a TP at the street crossing for a day (0730 --1930 hours) without accounting for shift changes.…”
Section: Introductionmentioning
confidence: 99%
“…The sun photometer at Pokhara is located near Pokhara city, which has significant local urban emission sources. A previous study at Pokhara found that the diurnal mean concentration of PM 10 was higher in the morning (07:30 a.m. to 11:30 a.m.) and evening (03:30 p.m. to 07:30 p.m.) than in the afternoon (11:30 a.m. to 03:30 p.m.) (Bashyal et al, 2008). The same pattern was also found in Kathmandu, 145 km east of Pokhara (Panday and Prinn, 2009).…”
Section: Xu Et Al: Similarities and Differences Of Aerosol Opticamentioning
confidence: 99%